Coping strategies in parents of children with disabilities: A case‐control study - Francisco J. Alós; Andrés García García; Miguel A. Maldonado (Brain and Behavior, 2022)
Abstract Introduction The aim of this article is to determine whether there are differences in the coping strategies of parents of children with disabilities (autism spectrum disorder or other disabilities) and children without disabilities, in reference to the most stressful situation they have experienced with their child in the last year. Method To conduct the study, a purposive sample selection based on case‐control characteristics was carried out, in which a total sample of 170 participants was recruited. Participants were assigned, according to their characteristics, to the group of parents of children without disabilities, with ASD or with other disabilities. An ad hoc sociodemographic questionnaire and the Coping Responses Inventory for adults were administered. Results The results obtained indicate that there are differences in the use of coping strategies between parents of children without disabilities and with disabilities but not between the two disability groups. Parents of children with disabilities have significantly higher scores on the four subscales defined as avoidance strategies, and on one subscale identified as an approach strategy. Conclusions Parents of children with disabilities use avoidance strategies, to a greater extent, during the most stressful situations they have experienced in the last year with their child. In addition, they tend to use avoidance strategies regardless of the type of disability their child has.